Research and trends in STEM education: a systematic analysis of publicly funded projects - Yeping Li; Ke Wang; Yu Xiao; Jeffrey E. Froyd; Sandra B. Nite (SpringerOpen, 2020)
Abstract Taking publicly funded projects in STEM education as a special lens, we aimed to learn about research and trends in STEM education. We identified a total of 127 projects funded by the Institute of Education Sciences (IES) of the US Department of Education from 2003 to 2019. Both the number of funded projects in STEM education and their funding amounts were high, although there were considerable fluctuations over the years. The number of projects with multiple principal investigators increased over time. The project duration was typically in the range of 3-4 years, and the goals of these projects were mostly categorized as "development and innovation" or "efficacy and replication." The majority of the 127 projects focused on individual STEM disciplines, especially mathematics. The findings, based on IES-funded projects, provided a glimpse of the research input and trends in STEM education in the USA, with possible implications for developing STEM education research in other education systems around the world.